Integral assessment of pollution in the Suquía River (Córdoba, Argentina) as a contribution to lotic ecosystem restoration programs - Merlo, Carolina (2011)
The Suquía River lower-middle basin (Córdoba, Argentina) is subject to a strong anthropic impact because it receives pollutants from different sources (industries, wastewaters, heavy traffic, agricultural land use, etc.). We have assessed the degree of watershed degradation of Suquía River lower-middle sections through the analysis of different ecosystem compartments (air, water, riparian soil, sediments and biota), in order to provide useful data to be considered in future river restoration programs. Four study sites were selected along the river (La Calera city, Córdoba city, Corazón de María village and Río Primero city) which were sampled during the low- and high-water flow periods. We analyzed: a) chemical and physical characteristics of water, sediments, and riparian soil; b) heavy metal content of water and sediments, and c) semi-volatile organic compounds in air. Besides, pollutant bioindicators such as fish assemblages, lichens (Usnea amblyoclada), vascular plants (Tradescantia pallida), and microorganisms (fecal coliform and Escherichia coli) were used to further assess the status of the river. All analyzed ecological compartments were affected by water pollution, particularly, fish assemblages, sediments and riparian soils by heavy metal and coliform bacteria. Moreover, we detected a possible contribution of sulfur and a high pollutant content in air that merit further research about other air-water exchanges. Accordingly, we strongly suggest that an action to restore or remediate the anthropic effect on the Suquía River be extended to all possible compartments along the river.